Marketing Strategy Based on Physical Evidence at Singaraja Army Hospital - Nurrahim, Firman; Syaodih, Erliany; Veranita, Mira (Universitas Islam Lamongan, 2024)
Hospitals as healthcare providers have now shifted towards a profit-oriented approach. The wide variety of services offered by hospitals to patients makes patients more selective in choosing products from providers that meet their needs and expectations. In marketing strategy, there are many efforts, one of which is through physical evidence. This study aims to analyze the marketing strategy based on physical evidence at Tk. IV Singaraja Hospital. This research uses a qualitative method. Research informants were selected using purposive sampling techniques, with the main informants consisting of the hospital director, head of the marketing unit, head of the outpatient unit, and head of the inpatient unit, as well as 10 patients for triangulation. Data collection was carried out through observation, questionnaires, interviews, and document analysis. The research findings revealed that the hospital's exterior facility still uses old buildings, the interior facility has well-maintained interior design, and the other tangible elements, such as pamphlets, brochures, and staff uniforms, are already provided by the hospital. Keywords: Marketing Strategy, Physical Evidence.